Description of the larva and pupa of Phileurus truncatus (Palisot de Beauvois, 1806) (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) with a key to described third instars of New World Phileurini - Arguez, Katherine M.; Moore, Matthew R.; Branham, Marc A. (Zootaxa, 2017)
The third instar and pupa of Phileurus truncatus (Palisot de Beauvois, 1806) (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) is described for the first time based on specimens from Florida, United States of America. An identification key to the third instars of New World Phileurini is also provided.